Клонування та експресія білків Mycobacterium bovis MPB63 і MPB83 у клітинах Escherichia coli - Редчук, Т.А.; Олійник, О.С.; Кабернюк, А.А.; Буркальова, Д.О.; Романюк, С.І.; Колибо, Д.В.; Комісаренко, С.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Gene fragments mpb83 and mpb63 from Mycobacterium bovis BCG were ampliﬁed using PCR. Plasmids containing mpb63 and mpb83 fragments have been constructed using the expressi- on vector pET24a (Novagen). Expression of recombinant proteins was obtained in E. coli Rosetta (DE3) сеlls under control of strong T7 promoter. Lysates were analyzed by immu- noblotting with anti HisTag conjugate. His-Tag fusion proteins were puriﬁed with batch metal affіnity chromatography under denaturative conditions. Results are expected to lay groundwork for the further development of improved diagnostic tools or vaccines against human and bovine tuberculosis.